Implementation of Heaven Theme Study in the Spirit of Worship: Implementasi Kajian Tema Surga dalam Semangat Beribadah - khoiri, khoiri (Procedia of Engineering and Life Science, 2024)
Worship is a central aspect of religious life practiced by believers with the aim of drawing closer to the Creator and adhering to the teachings of their faith. In the journey of worship, the theme of paradise plays a significant role as a source of motivation and spiritual guidance. Paradise, viewed as the ultimate destination filled with eternal happiness, pleasure, and peace, holds importance across various religious beliefs. Implementing studies on the theme of paradise in the spirit of worship is relevant for deepening understanding, motivating, and enhancing the quality of believers' worship. This research employs a qualitative approach, combining literature analysis and field studies. The analysis reveals that understanding the concept of paradise significantly influences believers' worship spirit. The theme of paradise serves not only as a personal motivator but also reinforces religious values and shapes moral behavior and ethics within religious communities. Challenges in implementing studies on the theme of paradise include varying individual understandings and interpretations of religious texts.D iscussion highlights the need for harmonizing understanding of the concept of paradise, optimizing the implementation of paradise-themed studies in worship through religious education and community activities, strengthening religious values through religious education programs, and addressing challenges through open dialogue and contextual approaches. This research contributes to a deeper understanding of implementing studies on the theme of paradise in the spirit of worship and proposes steps for developing more meaningful and directed worship practices within the religious context.